The effects of carpal tunnel syndrome on sleep quality (Annals of Medical Research, 2021)
Aim: Carpal tunnel syndrome (CTS) is the most common mononeuropathy of the upper extremities. The aim of this study was to investigate the relationship between different compression levels and sleep quality in patients with clinically and electrophysiologically diagnosed CTS.Material and Methods: Patients with CTS diagnosed by electroneuromyographic evaluation and healthy controls were included in the study. Demographic characteristics and disease symptoms were recorded carefully. The Boston Carpal Tunnel Questionnaire [symptom severity scale (SSS) and functional status scale (FSS)] was used to assess the severity of symptoms. Pittsburgh Sleep Quality Index (PSQI) was used to evaluate sleep quality and disorders.Results: A total of 94 CTS patients (80 female, 14 male) and 33 healthy controls were included. The median ages were similar among the groups (patient vs. control, mild-CTS vs. moderate-CTS, unilateral CTS vs. bilateral CTS; p = 0.11, p = 0.54, p = 0.22, respectively). The mean PSQI of patient group was higher than control group (7.81 ± 3.97 vs. 3.66 ± 2.08, p=0.000). While PSQI values were significantly different (p= 0.03) between unilateral-CTS and bilateral-CTS patients, no significant difference was observed in Boston-SSS, Boston-FSS, and total Boston values (p= 0.51, p= 0.29, p= 0.34 respectively). There was no significant difference between patients with mild-CTS and those with moderate-CTS in terms of PSQI, Boston-FSS, Boston-SSS, and total Boston values (p= 0.61, p= 0.54, p= 0.62, and p= 0.53 respectively). There was a positive correlation between PSQI and Boston-SSS, Boston-FSS, and total Boston values (p 0.001). Conclusion: Sleep quality was significantly affected in CTS patients, with a significant decrease in sleep time. While an increase in electrophysiological severity in patients with CTS did not affect the sleep quality, an increase in symptom severity decreased the sleep quality, with the greatest effect observed in patients with bilateral CTS.
Keywords: Carpal tunnel syndrome; sleep disorder; electromyography; sleep quality; symptom severity